Application of 1-octanol in the extraction and GC-FID analysis of volatile organic compounds produced in biogas and biohydrogen processes - Pavini, Weslei D. [UNESP]; Ferreira, João V.S.; Flumignan, Danilo L. [UNESP]; Maintinguer, Sandra I. [UNESP]; Oliveira, José E. [UNESP]; Sequinel, Rodrigo [UNESP] (My University, 2025)
Information about the volatile organic compounds generated in biogas and hydrogen production bioreactors is essential to elucidate the metabolic routes and varying yields of CH4 and H2 processes. In this work, the determination of 12 compounds (acetone, methanol, ethanol, 1-propanol, 1-butanol, and acetic, propanoic, butyric, isovaleric, valeric, caproic, and lactic acids) was performed by gas chromatography, after a vortex-assisted liquid–liquid microextraction (VALLME) procedure using 1.2 mL of crude sample and 400 µL of 1-octanol. Optimization of the separation process was performed, considering the solvent viscosity. The analytical curves were validated using ANOVA, demonstrating satisfactory precision and accuracy. Selectivity was confirmed by GC–MS analysis, which allowed the detection of glycerol, 1,3-propanediol, and 1,3-butanediol in some samples. Methanol levels exceeded the upper limit of quantification, with acetic acid and ethanol being the predominant compounds in the analyzed reactors. An additional investigation was conducted to assess potential interferences for lactic acid. The developed method employs a biodegradable extraction solvent, without any need for a dispersing solvent, and involves a single chromatographic run, without any derivatization steps.
Keywords: Fermentation; Lactic acid; Octanol; Short-chain fatty acids